A Neurosociological Theory of Culturally and Structurally Situated Cognition and Ethno-Racial Stress - Firat, Rengin B. (Frontiers in Sociology, 2021)
A longstanding body of literature reveals that experiences of discrimination and exclusion lead to health disadvantages by increasing physiological stress responses both in the body and the brain. However, a sociological view that takes into account structurally and culturally shaped biological processes is missing from the literature. Building on recent literature from the sociology of morality and values and the dual process model of culture, this paper proposes and provides preliminary evidence for an applied theory of culturally situated moral cognition as a coping mechanism with ethno-racial stress. I focus on values as they help cope with ethnicity and race related stress such as discrimination. Using functional neuroimaging data, I offer evidence that values operate through both explicit (controlled and conscious) processes recruiting brain regions like the dorsal prefrontal cortex, and implicit (automatic and non-conscious) processes recruiting regions like the ventromedial prefrontal cortex, to help cope with exclusion and discrimination.